2013
DOI: 10.1155/2013/236903
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Susceptibility of Candida Species to Four Antifungal Agents Assessed by the Reference Broth Microdilution Method

Abstract: This study was performed to determine the distribution of Candida species isolated from the blood cultures of the patients hospitalized in our hospital and to investigate their antifungal susceptibility. Candida strains were identified at species level by using classical methods and API ID 32C (bioMerieux, France) identification kits. The susceptibility of the strains to amphotericin B, fluconazole, voriconazole, and caspofungin was evaluated by using the reference broth microdilution method in document M27-A3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
30
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 22 publications
15
30
1
Order By: Relevance
“…This is in accord with most studies from our region [12][13][14][15][16][17][18][19][20][21][22][23][24] and from different parts of the world [31,34,35], where all Candida isolates exhibited high susceptibility to amphotericin B, with MICs of up to 1 mg/L. In contrast, the majority of the isolates in our study showed high levels of resistance (35%-79%) to itraconazole.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is in accord with most studies from our region [12][13][14][15][16][17][18][19][20][21][22][23][24] and from different parts of the world [31,34,35], where all Candida isolates exhibited high susceptibility to amphotericin B, with MICs of up to 1 mg/L. In contrast, the majority of the isolates in our study showed high levels of resistance (35%-79%) to itraconazole.…”
Section: Discussionsupporting
confidence: 92%
“…Nonetheless, data concerning the profile and antifungal susceptibility of Candida spp. are relatively few in some Arab countries [12][13][14][15][16][17][18][19] and other countries in the region [20][21][22][23][24]. In Lebanon, only one study exists, which was published 17 years ago [25]; thus, this subject warrants an update.…”
Section: Introductionmentioning
confidence: 99%
“…Antifungal susceptibility is highly important for management of patients with candidemia. The results of this study showed that all isolated Candida species were susceptible to amphotericin B, which is in agreement with the results of many other studies [24][25]. However, the increased usage of antifungal agents may contribute to increased occurrence of resistance in some Candida species more than others [26].…”
Section: Discussionsupporting
confidence: 92%
“…Eksi et al [24] in Turkey, found that 47.7% of their isolates from candidemia cases were C. albicans, followed by C. parapsilosis (36.9%) and other Candida species represented by 15.4%. Chi et al [7] in Taiwan, reported that C. albicans represented 43.5%, meanwhile, non-albicans spp.…”
Section: Discussionmentioning
confidence: 98%
“…In the study by Eksi et al [26] conducted in our region, Candida species were typed and tested for antifungal susceptibility. However, since the risk factors were not evaluated in this study, our study becomes prominent as the first one to take these factors into consideration.…”
Section: Discussionmentioning
confidence: 99%